Homes : a refugee story - Al Rabeeah, Abu Bakr, 2001-; Yeung, Winnie, 1982- (Freehand Books, 2018)
The story of Abu Bakr al Rabeeah, a young boy whose family moved from Iraq to Syria just before the start of the Syrian civil war. In 2014 his family finally found safety in immigrating to Edmonton, Canada.